MASS TRANSFER IN ECLIPSING BINARY STARS - Karetnikov, V. G.; Menchenkova, E. V.; Nazarenko, V. V. (Одеські астрономічні публікації, 2017)
Analysis of the properties of the eclipsing binary stars shows, that the stream-like mechanism of the mass transfer switches on at a contact evolutionary stage, preceding to a stage of binaries with a subgiant. The computations of the gas streams near the inner Lagrangian point have been made for the intermediate-mass contact systems of the early spectral classes (CE - systems). The properties of the streams are discussed and the conclusions are done concerning the evolutionary stage of the stars of this type.